A patent review of histone deacetylase 6 inhibitors in neurodegenerative diseases (2014-2019). (1st February 2020) - Shen, Sida; Kozikowski, Alan P.
ABSTRACT: Introduction : Histone deacetylase 6 (HDAC6) is unique in comparison with other zinc-dependent HDAC family members. An increasing amount of evidence from clinical and preclinical research demonstrates the potential of HDAC6 inhibition as an effective therapeutic approach for the treatment of cancer, autoimmune diseases, as well as neurological disorders. The recently disclosed crystal structures of HDAC6-ligand complexes offer further means for achieving pharmacophore refinement, thus further accelerating the pace of HDAC6 inhibitor discovery in the last few years. Area covered : This review summarizes the latest clinical status of HDAC6 inhibitors, discusses pharmacological applications of selective HDAC6 inhibitors in neurodegenerative diseases, and describes the patent applications dealing with HDAC6 inhibitors from 2014–2019 that have not been reported in research articles. Expert opinion : Phenylhydroxamate has proven a very useful scaffold in the discovery of potent and selective HDAC6 inhibitors. However, weaknesses of the hydroxamate function such as metabolic instability and mutagenic potential limit its application in the neurological field, where long-term administration is required. The recent invention of oxadiazole-based ligands by pharmaceutical companies may provide a new opportunity to optimize the druglike properties of HDAC6 inhibitors for the treatment of neurodegenerative diseases.